P14.17 Differentiation of treatment-related changes from tumor progression: A direct comparison between dynamic FET PET and ADC values obtained from DWI MRI. (6th September 2019) - Werner, J; Stoffels, G; Lichtenstein, T; Borggrefe, J; Lohmann, P; Ceccon, G; Fink, G R; Langen, K; Kabbasch, C; Galldiks, N
Abstract: BACKGROUND: Following brain cancer treatment, the capacity of anatomical MRI to differentiate neoplastic tissue from treatment-related changes (e.g., pseudoprogression) is limited. This study compared apparent diffusion coefficients (ADC) obtained by diffusion-weighted MRI (DWI) with static and dynamic parameters of O-(2-[ 18 F]fluoroethyl)-L-tyrosine (FET) PET for the differentiation of treatment-related changes from tumor progression. MATERIAL AND METHODS: Forty-eight pretreated high-grade glioma patients with anatomical MRI findings suspicious for progression (median time elapsed since last treatment, 16 weeks) were investigated using DWI and dynamic FET PET. Maximum and mean tumor-to-brain ratios (TBRmax, TBRmean) as well as dynamic parameters (time-to-peak and slope values) of FET uptake were calculated. For mean ADC calculation, regions-of-interest analyses were performed on ADC maps calculated from DWI co-registered with the contrast-enhanced MR image. Diagnoses were confirmed neuropathologically (21%) or clinicoradiologically. Diagnostic performance was evaluated using receiver-operating-characteristic analyses or Fisher's exact test for a combinational approach. RESULTS: Ten of 48 patients had treatment-related changes (21%). The diagnostic performance of FET PET was significantly higher (threshold for both TBRmax and TBRmean, 1.95; accuracy, 83%; AUC, 0.89±0.05; P<0.001) than that of ADC values (threshold ADC, 1.09x10 -3 mm 2 /s; accuracy, 69%; AUC, 0.73±0.09; P=0.13). The addition of static FET PET parameters to ADC values increased the latter's accuracy to 89%. The highest accuracy was achieved by combining static and dynamic FET PET parameters (93%). CONCLUSION: Data suggest that static and dynamic FET PET provide valuable information concerning the differentiation of early treatment-related changes from tumor progression and outperform ADC measurement for this highly relevant clinical question.